Hudson Taylor in early years the growth of a soul - Taylor, Howard; China Inland Mission; Taylor, Mary Geraldine, 1862-1949 (London, UK Morgan and Scott, 1911)
Includes bibliographical references and index.
Mrs Taylor, (Mary Geraldine Guiness) of Brethren background.
Keywords: Missions -- biography; China -- missions